Effects of different degrees of deacetylation and levels of chitosan on performance, egg traits and serum biochemistry of laying hens - Farivar, Afshin; Atay, Alp; Şahan, Zeynep; Serbester, Uğur; Yenilmez, Fatma; Tekeli, Ahmet; Küçükgülmez, Aygül; Kadak, Ali Eslem; Celik, Mehmet; Uzun, Yusuf; Kutlu, Hasan Rüştü; Baykal Çelik, Ladine (Informa UK Limited, 2022)
The present study was conducted to evaluate whether the deacetylation degree of chitosan (low: 70% vs. high: 90%) and its dietary level (0, 200, 400, 800, 1600 mg/kg diet) would affect laying performance, faeces viscosity, egg quality, egg and serum biochemistry of layers. For the experimental feeding period of 8 weeks, 140 four weeks old Hisex Brown layers were divided into 10 treatment groups, comprising 14 birds each. The birds were housed in individual cages in a complete randomised design. Performance was assessed by recording feed intake, egg weight, daily egg production, egg quality and egg biochemistry. Serum biochemistry parameters were determined at the beginning and end of the experiment and faeces viscosity at the end of the experiment. Feed conversion ratio and faeces viscosity were deteriorated by increased level of chitosan. Lightness of egg yolk was significantly increased in animals receiving high-degree deacetylated chitosan compared to low-degree deacetylated chitosan. Yellowness of egg yolk was affected by interaction of deacetylation degree and level of chitosan. Yolk cholesterol concentration was lower in groups receiving high deacetylated chitosan by increasing chitosan level, while laying hens fed low deacetylated chitosan had a higher level of yolk cholesterol. A significant interaction between degree of deacetylation and chitosan level was determined for serum glucose and calcium concentration. Serum total antioxidant content increased with higher levels of dietary chitosan. In conclusion, dietary level or different degrees of deacetylated chitosan may reduce yolk cholesterol and improve serum antioxidant status. However, feed conversion ratio and faeces viscosity were impaired by increasing levels of chitosan supplementation, and lightness of yolk was increased by supplementation of chitosan with a high degree of deacetylation.
Keywords: Chitosan; Cholesterol; Dietary Supplements; Animals; Female; Animal Feed; Chickens; Antioxidants; Diet; 2. Zero hunger